2017
DOI: 10.1007/s10792-017-0730-0
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial changes following a single session of selective laser trabeculoplasty for pseudoexfoliative glaucoma

Abstract: Effect of a single session of SLT on corneal endothelium of PEG patients appears to be transient, and superior cornea was more affected than central and inferior cornea. All parameters returned to pre-SLT values at 1 month after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…Our study confirmed that higher baseline IOP predicts higher hypotensive response and higher percentage of IOP reduction from baseline [28,29].…”
Section: Discussionsupporting
confidence: 86%
“…Our study confirmed that higher baseline IOP predicts higher hypotensive response and higher percentage of IOP reduction from baseline [28,29].…”
Section: Discussionsupporting
confidence: 86%
“…[16] who also found a significantly higher CV in uveitis in patients with AS. Similarly, a recent study by Örnek and Örnek [18] reported that CD was significantly lower and CV was significantly higher in the RA group than in healthy subjects…”
Section: Discussionsupporting
confidence: 52%
“…13 Ornek et al have reported other causes that can lead to decreased corneal endothelial cell density like pseudoexfoliation (2510.6±220) when compared to control Group (2740.4±330) and some eyes after treatment with SLT (selective laser trabeculoplasty) 2488.2±348. 14 We have observed increased AVG in patients with uveitis than in healthy subjects. Guclu et al had similar observations regarding AVG in their study.…”
Section: Discussionmentioning
confidence: 66%